Histamine dihydrochloride for maintaining remission in acute myeloid leukemia. (April 2014) - Horowitz, Netanel A; Rowe, Jacob M
SUMMARY : Maintaining complete remission in patients with acute myeloid leukemia (AML) is a great challenge. Targeting the remaining malignant clones, using different regimens of chemotherapeutic agents did not prove to be fruitful. Host residual leukemia stem cells may be eradicated by donor immune cells in case of allogeneic stem cell transplantation. However, only a minority of AML patients may benefit from this procedure. IL-2 is very well known in its ability to enhance activation and proliferation of natural killer and T cells, albeit in the clinical setting this effect is suppressed by myeloid cells derived oxygen species. Histamine dihydrochloride can inhibit myeloid cells activity, therefore reaugment antileukemic natural killer/T-cell cytotoxic activity. This review summarizes different strategies to maintain complete remission in AML patients focusing on the use of histamine dihydrochloride/IL-2 treatment.